Analisis faktor memilih karier jabatan fungsional pustakawan di Perpustakaan Pusat Universitas Padjadjaran - Muhammad Zeinuri Rahyudi; Mulyani Mulyani; Yulianti Yulianti (Jurnal Kajian Informasi dan Perpustakaan, 2019)
Choosing the type of job for a civil servant is the first step to establishing a career. A civil servant can opt for several careers. One of which is the functional librarian, through the librarian at the skill level and the librarian at the expertise level. Many factors are the background of career selection for civil servants who choose the functional librarian so that the librarian profession can develop both in quantity and quality. This study aimed to determine the civil servant's factors choosing the functional librarian at Universitas Padjadjaran in Bandung. This research used a descriptive method through a qualitative approach, by distributing questionnaires conducted from December 7, 2017, to December 15, 2017. The total number of population sampel was 100 people. Based on the study results, the conclusions are that many of the a civil servant choose the functional librarian due leadership encouragement, to the opportunity to move up the rank/class faster and the expectation of increased income. The job for a civil servant choose the functional librarian because of the opportunity to move up the rank faster to increase income. In addition, educational staff as functional positions to get a level or a career that is better than the job previous condition. Meanwhile, the job for a civil servant basically already have expertise in the field of library science in the different degrees.